EFEKTIVITAS PEMUNGUTAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH - Mela Sari; Indah Pertiwi; Mardansyah .; Yulia Wiji Astika (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2021)
TThis research was motivated by the existence of non-metallic mineral and rocks that did not have a mining permit, there was no coordination with the agency in order to get data about the mining location and taxpayers did payment not in actual conditions. The aim of this research was to know the effectiveness of collecting taxes on non-metallic mineral and rocks in increasing Local Origi-nal Income (PAD) by the Regional Tax and Retribution Management Agency (BPPRD) of Bungo Regency and the obstacles faced in collecting this taxes. The method used in this research was descriptive qualitative. The population in this research were all employees and taxpayers of non-metallic minerals and rocks with total sample were 14 by using purposive sampling technique. The data collection techniques were observation, interviews, and documentation. The results of this research showed that the collection of taxes on non-metallic minerals and rocks in increasing the PAD of Bungo Regency by BPPRD had not been effective, it was showed by the contribution of revenue non-metallic minerals and rocks to PAD for the last 5 years on average 1.12%. That was disproportionate to the potential tax on non-metallic minerals and rocks that have not been properly excavated due to various obstacles, namely inadequate facilities and infrastructure, lim-ited resources, and low awareness of taxpayers.